The Effect of Physical Exercise according to a Programme for the Development of Flexibility in the Motor Abilities of Young Football Players - Sami Sermaxhaj; Fitim Arifi; Jeton Havolli; Fadil Luta; Imran Isufi (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
This research aims to establish the effect of flexibility exercise on the motor abilities of young football players. The total number of participants was 68 young football players (beginners, pioneers, and cadets) from the Ramiz Sadiku Football Club in Prishtina, Kosovo. The participants were divided into control and experimental groups. The research implemented seven variables for estimating motor abilities. The effect of physical exercise according to the programme of flexibility on the motor abilities of young football players was investigated using uni-variant analysis. The course of preparatory and competition period training programme was conducted three times per week, for both groups. Only the manner of execution of the experimental programme was different (17 exercises of static stretching) for the development of flexibility, which was conducted only with the experimental group within the frame of increased duration by the end of the training. The results acquired show that programme conducted for the development of flexibility (exercised of static stretching) has a statistically significant effect only on flexibility variable "sit-and-reach test" with the experimental group of cadets, and with no statistically essential influence on the motor abilities of beginners, pioneers, and cadets. Therefore, it can be confirmed that static exercises have an essential effect on the improvement of flexibility of participants older than 15 years old, but without positive or negative effects on other variables of the motor abilities of young players.